2022
DOI: 10.47405/mjssh.v7i11.1989
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Awareness and Public Participation: A Driving Force for Environmental Protection in Sierra Leone

Abstract: Countries globally have enjoyed unprecedented economic growth in the present times, even though this economic growth has its consequence on the environment and public health. This development has seen the unrestricted cutting down of forests, waste generation, extinction of species, etc. Addressing these predicaments, the United Nations, at the global level, has urged States to develop and enforce environmental legislation, policies, and strategies. As a member of the United Nations, Sierra Leone has promulgat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…This study focuses on the Malaysian public intention to manage e-waste. The study results can provide information and help responsible bodies plan policies, regulations, or better legislation in the future (Jalloh, Dahalan, & Khalid, 2022). E-waste produced from non-industrial sectors, especially houses such as televisions, air conditioners, washing machines, refrigerators, and others, yet regulated correctly in existing regulations, resulting in most e-waste being disposed of inappropriately (Beula & Sureshkumar, 2021).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…This study focuses on the Malaysian public intention to manage e-waste. The study results can provide information and help responsible bodies plan policies, regulations, or better legislation in the future (Jalloh, Dahalan, & Khalid, 2022). E-waste produced from non-industrial sectors, especially houses such as televisions, air conditioners, washing machines, refrigerators, and others, yet regulated correctly in existing regulations, resulting in most e-waste being disposed of inappropriately (Beula & Sureshkumar, 2021).…”
Section: Introductionmentioning
confidence: 93%
“…Empirical studies have found that many youths are unaware of the e-waste phenomenon and its effects . Awareness of the effects of e-waste should be a main priority, and national leaders must shape and apply pure and moral values to the young generation (Jalloh, Dahalan, & Khalid, 2022). To improve e-waste awareness, educators and practitioners need to provide information on e-waste, which needs to be done as early as preschool age.…”
Section: The Influence Of Information On the Intention For E-waste Re...mentioning
confidence: 99%